The Positive Loop at Work: A Longitudinal Long-Term Study of Transformational Leadership, Group Passion, and Employee Results - Mindeguia, Rosa; Aritzeta, Aitor; Garmendia, Alaine; Aranberri, Ainara (Frontiers in Psychology, 2021)
Positive psychology and positive organizational behavior studies recognize that leadership is extremely important for generating positive well-being. Despite the frequently reported significant positive correlations, the causal long-term relationship between leadership, positive high intense affect, and employee results remains unclear. The main objective of this study was to analyze the long-term (longitudinal) relation of transformational leadership and positive high-intensity emotions with employee group satisfaction, commitment, and proactive behavior. We built a longitudinal structural equation model to test a mediation model with two time points; 2,480 workers from 166 work units completed questionnaires at both time points. Our results reveal that positive high-intensity emotions mediate the relation between transformational leadership and proactive behavior of workers, the bidirectional relations between the variables were also analyzed. The present study is, to our knowledge, the first analyzing the long-term effect of TFL and collective high-intensity emotions on worker’s results longitudinally. Our findings reflect the great complexity of affect and affect-related results in organizations and highlight the need for more longitudinal research to clarify emotional processes at work.